Disseminated aspergillosis with mediastinal invasion causing fatal stroke in an immunocompetent young man - Robert Yarham; Rudy Goh; Eamon P. Raith; Krishnaswamy Sundararajan; Timothy Kleinig (Case Reports in Neurology, 2024)
Introduction: Aspergillus flavus is a common cause of aspergillosis. Case presentation: A previously fit and well, immunocompetent 27-year old male living in Australia developed disseminated Aspergillus flavus complex infection with mediastinal and cardiac invasion, superior vena cava obstruction and stroke, with fatal haemorrhagic transformation. Conclusion: Aspergillus Flavus is a rare but important cause of serious disease in the immunocompetent.